P170 Heart Rate Recovery At One Minute Following Incremental Shuttle Walk Test Predicts Outcome In Pulmonary Hypertension. (10th November 2014) - Billings, CG; Hurdman, J; Austin, M; Armstrong, I; Elliot, CA; Condliffe, RA; Kiely, DG
Abstract : Background: Heart-rate recovery during the first minute of rest (HRR1) after a six minute walk test (6MWT) has been shown to be a strong predictor of clinical worsening in patients with pulmonary arterial hypertension. 1 No data as yet has been published regarding the utility of HRR1 as a predictor of mortality. Aim: To assess the prognostic value of HRR1 after an Incremental Shuttle Walk Test (ISWT) in patients with pulmonary hypertension (PH). Methods: Data was retrieved for consecutive cases of PH diagnosed in our unit from 2001–2010. ISWT was performed routinely as part of baseline assessment according to a modified protocol of Singh et al . 2 Only treatment-naive patients with ISWT and HRR data from -90 to +30 days from date of diagnosis were included. HRR1 was defined as the difference between maximum heart rate during the ISWT and heart rate after 1 min of rest following the termination of ISWT. Results: Data was available for 491 patients (including patients from each of the 5 main PH diagnostic groups). HRR1 correlated significantly with ISWT distance, highest heart-rate, maximal change in heart-rate, % predicted carbon monoxide diffusion (DLco%pred), pulmonary vascular resistance, cardiac output and mixed venous oxygen saturation (p all ≤0.01). Using a cut-off point of 18bpm the Kaplan Meier graph for survival for patients with HRR1 >18 bpm (n = 179) was significantly better than HRR1 ≤18 bpm (n = 312), p = 0.007 (Figure 1 ) for all patients and for diagnostic Groups 1 and 2 separately (p = 0.045, p = 0.006). Using univariate Cox proportional hazard analysis for all patients HRR1 (continuous data) had a Hazard Ratio for mortality (HR) of 0.990 with a confidence interval (CI) of 0.962–0.997, p = 0.008. Compared to patients with HRR1 >18, those with HRR1≤18 had a HR of 1.559 (CI 1.127–2.156) p = 0.007. Grouping patients by median distance walked and HRR1–18 demonstrated that the HRR1 proved a useful predictor only in patients who walked less than 180 m. Conclusion: HRR1 following ISWT predicts outcome in patients with pulmonary hypertension with more severe disease. References: 1Minai OA et al . Am J Respir Crit Care Med . 2012;185:400-408 Singh et al . Thorax 1992;47:1019–1024